Arsitekur Multikultural pada Fasad Masjid Agung Sang Cipta Rasa Cirebon - Lia Rosmala Schiffer; Atiek Suprapti Budiarto; R. Siti Rukayah; Yudi Nugraha Bahar (Universitas Sebelas Maret Surakarta, 2022)
The Great Mosque of Sang Cipta Rasa is located in front of the Kasepuhan Palace Complex to the west of the square in front of the Kasepuhan Palace, Cirebon. The construction of this mosque was assisted by Sunan Bonang and Sunan Kalijaga. The physical work was carried out by the former Majapahit architect, Raden Sepat, assisted by 500 of his troops who were former Majapahit troops. (Budi, 2015). The religious shift from the end of the Hindu-Buddhist era to the entry of Islam affected the facade of the Great Mosque of Sang Cipta Rasa in Cirebon. Elements forming a building facade generally include the site entrance, ground floor zone, arcades, windows and building entrances, fences, roofs, and signs. and ornaments. This study uses a descriptive technique in its explanation. The research method used is a qualitative method, by observing the variable character of the facade of the Great Mosque of Sang Cipta. The purpose of this paper is to examine how the facade design of the Great Mosque of Sang Cipta on doors, windows, walls, and ornaments contains elements and components of Hindu, Javanese, Chinese and Islamic historical influences.